2018
DOI: 10.1016/j.chemosphere.2018.06.118
|View full text |Cite
|
Sign up to set email alerts
|

Increased exposure to pesticides and colon cancer: Early evidence in Brazil

Abstract: Environmental factors may increase colon cancer (CC) risk. It has been suggested that pesticides could play a significant role in the etiology of this malignancy. As agriculture is one of the mainstays of the Brazilian economy, this country has become the largest pesticides consumer worldwide. The CC burden is also increasing in Brazil. Herein, we examined data from the Brazilian Federal Government to determine whether CC mortality and pesticide consumption may be associated. Database of the Ministry of Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 53 publications
0
17
1
5
Order By: Relevance
“…Our results are inconsistent with those of a study that suggests pesticide exposure as another explanatory factor 38. Agricultural areas with high pesticide use are clustered in the North and Southeastern regions of our study area.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are inconsistent with those of a study that suggests pesticide exposure as another explanatory factor 38. Agricultural areas with high pesticide use are clustered in the North and Southeastern regions of our study area.…”
Section: Resultscontrasting
confidence: 99%
“…Although this classification is for lung cancer, it is relevant to question the impact of such pollution on CRC. Specifically, some traffic-related pollutants, such as NO 2 and benzene, are suspected to be involved in the pathogenesis of CRC 37,38. High-level exposure to diesel emissions may increase the risk of rectal cancer in Canadian men,39 not colonic cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the excessive use of pesticides in Brazil can affect the environment and human health (Waichman et al 2002). Pesticides can cause direct damage to the health of rural workers through cancer (Martin et al 2018) and hormonal disorders (Bernieri et al 2019) as well as other ailments. Moreover, several reviews and epidemiological studies have shown the damage to renal function from exposure to pesticides (Lee et al 2015; Lebov et al 2016; Valcke et al 2017; Prudente et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, organic food contains higher levels of nutrients and bioactive substances that improve consumers' health and wellness [10][11][12][13]. Organic diets have the benefit of exposing consumers to considerably lower levels of chemicals, which can cause several human diseases like cancer, autism, and infertility [14][15][16][17][18][19]. Data form pesticide residues' monitoring clearly show that foods from organic farming have lower levels of pesticide residues when compared with foods grown in conventional farming systems [20,21].…”
Section: Introductionmentioning
confidence: 99%